Simple formulas for the dynamic stiffness of pile groups. - Taherzadeh, Reza (Earthquake engineering & structural dynamics.)
Simple formulas are derived for the dynamic stiffness of pile group foundations subjected to horizontal and rocking dynamic loads. The formulations are based on the construction of a general model of impedance matrices as the condensation of matrices of mass, damping, and stiffness, and on the identification of the values of these matrices on an extensive database of numerical experiments computed using coupled finite element?boundary element models. The formulations obtained can be readily used for the design of both floating piles on homogeneous half-space and end-bearing piles and are applicable for a wide range of mechanical and geometrical parameters of the soil and piles, in particular for large pile groups. For the seismic design of a building, the use of the simple formulas rather than a full computational model is shown to induce little error on the evaluation of the response spectra and time histories.